American hustle [screenplay] - Singer, Eric Warren 1968-; Russell, David O. 1958- ([Verlag nicht ermittelbar], 2013)
A con man, Irving Rosenfeld, along with his seductive British partner, Sydney Prosser, is forced to work for a wild FBI agent, Richie DiMaso. DiMaso pushes them into a world of Jersey powerbrokers and mafia
Keywords: Swindlers and swindling / Drama; Mafia / New Jersey / Drama; United States / Federal Bureau of Investigation; Motion picture plays; Mafia; Swindlers and swindling; New Jersey; Drama; Drehbuch